Avaliação de ferramentas de geração automática de dados de teste para programas java: um estudo exploratório - Oliveira , Daniel Gomes de (2016)
Considering the high cost and large amount of time demanded by the activity generation tests in the software development process, the need a proposal to reduce both the time spent as the related costs testing activities is necessary. In this context, the use of tools or processes that make the activities of generation of more agile testing, less costly and meet demands for precision are key to companies operating in software development market can achieve their goals. Based on these information comes to questions regarding how to go about adopting a process that makes possible the achievement of objectives in order to meet the results mentioned previously, even with the difficulties of generating test data as a result of of programs input areas are infinite. There are different tools that use various strategies for generating test data, however, lacks evidence as the quality of these tools. In this context, the aim of this work is conducting an experimental evaluation of some automatic test data generators to identify which one offers the best cost / benefit in terms of effective in detecting defects number of generated test data, code coverage demanded by test data, and generation time of testing. At second step a third tool was included along manually generated tests. New test sets using three automatic generators and included the manually -generated sets project were generated. Finally, results were presented in terms of effectiveness and efficiency through the comparison between the four test sets .